التمرد النفسي لدى طلبة الجامعة (Journal Of Educational and Psychological Researches, 2013)
Current search targeted to:  1 - Measuring the psychological rebellion among the students of the university.  2 - Identify the significant differences in the degrees of psychological rebellion among members of the sample according to the variables of sex (male - female), specialty (Science - a human).      To achieve the objectives of the research chose researcher samples from the community of the first search for statistical analysis, has reached 400 students, and the second sample of the application of the final, has reached (480) students were selected randomly with simple check of equal value, and the researcher building a search tool double think, After the completion of the scale-building measures thinking double (34) paragraph, the researcher apply the measure to final application of sample size (480) students.     After statistical treatments of using the bag SPSS statistical research found the following results: -1 - The students of the university to have a mutiny myself.2 - did not show the effect of the interaction between sex variable in psychological rebellion among the students of the university.3 - that there is a difference in the level of insurgency psychological variable depending on the specialization favor of humanitarian Specialization. Accordingly, the researcher presented a set of recommendations and proposals, including:1 - urged the Ministry of Higher Education and Scientific Research Department of the supervision and evaluation of activating the role of psychological counseling centers in all universities under the supervision of specialized cadres.2 - urged academic institutions holding seminars and lectures through a strategy of preventive counseling, to reduce some unwanted behaviors, including psychological insurgency.3 - urged academic institutions attention to the activities and programs of social, cultural and sports in order to deepen the spirit of cooperation, tolerance and brotherhood among university students.